Test-Driven Development (TDD) for Point of Sale System at Bicycle Shop - Subhiyakto, Egia Rosi; Astuti, Yani Parti (Universitas Negeri Semarang, 2020)
The information technology systems are developing faster; one of its developments is a system to process the recording of sales data (Selling System). To support the selling process in Ali Cycle bicycle shop, which previously done manually, it needs a system to record the stock of goods, transaction, supplier, and sales report. There is a lot of model in building the system, one of the model is traditional development model, generally, the phase of this model is never-ending related to system problems or bugs, sometimes bugs are not found in the development but comes after practical use begins. A Point of Sale (POS) system with Test Driven Development (TDD) method has been built in which a test is written before the coding phase in a purpose of the codes, which are created, has passed the test, reducing the bug and it tests the system. The results show that all codes have passed the test; the test consists of 89 functions and 397 statements. Evaluation results of end-users testing showed that the majority of respondents strongly agree and agree with a system with an average rating of 94% for performance, 89% interface and 83% user satisfaction. The conclusion is, building a POS system using TDD method succeeded by producing a useful system as the requirement and expected system quality.